2020
DOI: 10.1155/2020/2387378
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated with the Differential Activity of Nondominant and Dominant Affected Hands in Patients with Poststroke Right Hemiparesis

Abstract: Objectives. Spontaneous arm use in patients with poststroke hemiparesis is crucial to the recovery of functional interaction. Patients with stroke and subsequent right hemiparesis have more difficulty adapting to a right-handed environment. The aim of this study was to use wearable devices to assess the asymmetry and difference in the amount of activity of the nondominant and dominant affected hands among patients with stroke and right hemiparesis. The real activity of both hands was measured to assess the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In this review, we also found that the asymptomatic PICC‐RT was more likely to occur in the left basilic vein than the right basilic vein (Bonizzoli et al., 2011 ). This finding might be explained by the fact that activity of the left arm is lower than that of the right arm for most people whose dominant hands are right hands (Ardon et al., 2014 ) and activity promotes blood circulation (Lee et al., 2020 ; Liu et al., 2018 ). When PICC is inserted on the left hand, the catheterization arm cannot get enough exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we also found that the asymptomatic PICC‐RT was more likely to occur in the left basilic vein than the right basilic vein (Bonizzoli et al., 2011 ). This finding might be explained by the fact that activity of the left arm is lower than that of the right arm for most people whose dominant hands are right hands (Ardon et al., 2014 ) and activity promotes blood circulation (Lee et al., 2020 ; Liu et al., 2018 ). When PICC is inserted on the left hand, the catheterization arm cannot get enough exercise.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation to this mismatch could be that when the affected hand is not the dominant hand, the effect of the hand's impairment on the overall function of the individual is less significant. The existing literature also supports this explanation -the dominance of the affected brain side after stroke has not been found to have a significant effect on function and quality of life (Nam et al, 2014;Lee et al, 2020). However, the dominance of the affected hand does have an impact on the impairment level; individuals with a dominant brain side stroke show less impairment compared to those with a non-dominant brain side stroke (Harris and Eng, 2006).…”
Section: Brain Side Dominancementioning
confidence: 92%
“…Moreover, WAMs are acceptable to clinicians and patients. [43][44][45] One of the most common and long-term morbidities associated with breast cancer treatment is lymphedema. 19 The assessment of lymphedema is complex, and there are many factors that should be considered.…”
Section: Discussionmentioning
confidence: 99%